2007
DOI: 10.1002/yea.1499
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic footprinting as a tool for discriminating between brewing yeasts

Abstract: The characterization of industrial yeast strains by examining their metabolic footprints (exometabolomes) was investigated and compared to genome-based discriminatory methods. A group of nine industrial brewing yeasts was studied by comparing their metabolic footprints, genetic fingerprints and comparative genomic hybridization profiles. Metabolic footprinting was carried out by both direct injection mass spectrometry (DIMS) and gas chromatography time-of-flight mass spectrometry (GC-TOF-MS), with data analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
66
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(69 citation statements)
references
References 41 publications
2
66
0
1
Order By: Relevance
“…This extends to natural populations that have multiple uncharacterized genetic changes, such as an accumulation of mutations, as well as sometimes extensive genetic differences such as pathogenicity islands (21), which may interact to give complex phenotypes. Molecular phylogenetic methods based on gene sequences have proved successful in classifying bacteria into taxonomic groupings, but these may not always correspond to easily identifiable phenotypes or ecotypes (29,33,48). Hence, additional methods for strain assessment that could be related to function would still be valuable.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This extends to natural populations that have multiple uncharacterized genetic changes, such as an accumulation of mutations, as well as sometimes extensive genetic differences such as pathogenicity islands (21), which may interact to give complex phenotypes. Molecular phylogenetic methods based on gene sequences have proved successful in classifying bacteria into taxonomic groupings, but these may not always correspond to easily identifiable phenotypes or ecotypes (29,33,48). Hence, additional methods for strain assessment that could be related to function would still be valuable.…”
mentioning
confidence: 99%
“…In contrast, exometabolome or supernatant profiling ("metabolic footprinting") is simple, and extracellular metabolites can exhibit very large changes in pool size (1,27,40,45). These multiple advantages mean that exometabolome analysis has already been used for a number of diverse applications, such as phenotyping of both single-gene deletion mutants and isolates from natural populations, although thus far mostly for fungi rather than bacteria (1,2,9,25,40,48).…”
mentioning
confidence: 99%
“…In fact, a genotype analysis of 651 S. cerevisiae strains revealed that ale strains were more closely related to wine and bread strains (above referred as Baker's yeast), than to lager brewer's yeast strains [36]. Reports of hybrids in ale yeasts showed that strains traditionally classified as S. cerevisiae may indeed be the result of hybridization events [37]. Ale beer has less representation in worldwide markets, and as a consequence less studies and information are available on the corresponding yeasts.…”
Section: Yeast Physiologymentioning
confidence: 99%
“…Highthroughput technologies such as Nuclear Magnetic Resonance (NMR), Infrared (IR) and Raman spectroscopy, chromatographic methods and mass spectrometry, generate complex data (''fingerprints'') based on chemical composition and metabolite profiles of micro-organisms (metabolome) [9][10][11][12][13]. Such metabolomic methods can detect genotypic and phenotypic differences even in closely related microorganisms and also in genetically modified strains [13][14][15][16][17], with greater discriminatory power than transcriptomics and proteomics [17,18]. Spectroscopic techniques characterise rapidly and simultaneously multiple chemical compounds in biological fluids [10,[19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%